Closed Incisional Negative Pressure Wound Therapy at Flap Suture Line: An Innovative Approach for Improving Outcomes in Suboptimal Wound Conditions - Naalla, Ravikiran; Bhushan, Smriti; Abedin, Minhaj Ul; Bichpuriya, Ashish Dhanraj; Singhal, Maneesh (Indian Journal of Plastic Surgery, 2020)
Background Persistent dead space following flap cover is a frequently encountered challenge following the reconstruction of complex wounds. It may lead to a hematoma, seroma, wound infection, and wound dehiscence. Wound dehiscence could be a devastating complication. Closed incisional negative pressure wound therapy (ciNPWT) over the surgical incisions was found to reduce surgical site infection (SSI) and wound dehiscence. We applied this principle at the closed flap suture line and through this article, we share the indications, technique, and outcomes.Methods A retrospective analysis (January 2018–June 2019), in which selected high-risk patients who underwent ciNPWT at the flap suture following complex reconstruction (pedicled or free flap) were included in the study. The indications include deep incisional/organ SSI after debridement and flap coverage, persistent dead space following flap coverage, chronic osteomyelitis. Patients were analyzed in the follow-up period in terms of complications, wound healing.Results Nine patients underwent ciNPWT over the flap suture line. The mean age was 32.2 years (range: 10–48 years). The mean duration of the NPWT application was 7.3 days (range: 3–21 days). Three of the nine patients had flap-related minor complications. One patient had marginal flap necrosis and required skin grafting, one patient had minor wound dehiscence (1 cm) which required secondary skin suturing and one patient had chronic discharging sinus related to osteomyelitis of ischium, which subsequently healed with antibiotics and local wound care. None of the patients had NPWT-related complications.Conclusion Closed incisional NPWT decreases the untoward effects of dead space following the reconstruction of complex wounds. The incidence of SSI and wound gaping can be reduced.
Keywords: closed incisional negative pressure wound therapy; wound healing; wound dehiscence